Problem Cased (Permasalahan) Dalam Pembelajaran Bahasa Inggris di Sekolah - Uzer, Yus Vernandes; Uzer, Yuspar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
English learning at an Elementary school in Indonesia has undergone a significant and very rapid revolution. In conducting learning English definitely problems arises, and the problems of English learning is actually long before the curriculum changes until the implementation of curriculum 2013. The strategy used in this study is classroom action research strategy with measures to hold action planning, observation or observation, carry out analysis and reflection. Data collection techniques used to obtain data in this study, among other tests, as well as direct observation. From the results of these studies concluded that learning by using the method of administration tasks can increase the activity of students in learning English, and learning outcomes in students of Class VI of SDN 93 Palembang to provide reinforcement and allow more students to participate in learning English.